Another Six-Node Triangular Element for Structural Analysis - HOANG THAT TON, Lan (Engineering Transactions, 2022)
A six-node triangular element is presented in this paper for structural analysis. With this approach, the approximation functions of the interpolation strategy are given by using the double interpolation procedure, which includes nodal values as well as averaged nodal gradients. The numerical results are, therefore, achieved following the proposed element. The efficiency of this element and its comparison is described by some fundamental examples. Better numerical solutions and smoother distributions of stresses not achieved by the standard elements will be provided when using this element. The computational time is also presented to overview the pros and cons of the proposed element. In fact, the new element’s computational time is higher than that based on the standard element because of the double interpolation procedure, but one does not need post-processing of any smoothing operation.